2015
DOI: 10.1007/s11368-015-1131-5
|View full text |Cite|
|
Sign up to set email alerts
|

Candidatus Brocadia and Candidatus Kuenenia predominated in anammox bacterial community in selected Chinese paddy soils

Abstract: Purpose Anammox bacteria have been widely investigated in both natural aquatic habitats and wastewater treatment reactors. However, their distribution in agricultural ecosystems which receive high reactive nitrogen input is hardly known. This study aims to examine the distribution and diversity of anammox bacteria in different Chinese paddy soils and along soil profile horizons. Materials and methods DNA was extracted from paddy soils which were collected from ten sites and along four soil depth horizons (0-20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 35 publications
(44 reference statements)
2
12
0
Order By: Relevance
“…Similar to previous reports, Candidatus Brocadia dominated in this paddy soils fields (Bai et al, 2015;Yang et al, 2015). Bacteria of this genus harbor diverse metabolism (Gori et al, 2011), with the ability to use short-chain organic acids as electron donors instead of NH 4 þ , making it highly adaptable.…”
Section: Discussionsupporting
confidence: 86%
“…Similar to previous reports, Candidatus Brocadia dominated in this paddy soils fields (Bai et al, 2015;Yang et al, 2015). Bacteria of this genus harbor diverse metabolism (Gori et al, 2011), with the ability to use short-chain organic acids as electron donors instead of NH 4 þ , making it highly adaptable.…”
Section: Discussionsupporting
confidence: 86%
“…4). In many previous studies, the detection frequency of Candidatus Jettenia was much lower in comparison to Candidatus Brocadia and Kuenenia, and was even undetectable in some paddy soils (Bai et al, 2015;Yang et al, 2015). However, it was also shown that Candidatus Jettenia occupied a large portion of anammox bacterial Table 2 The detected OTUs and diversity indices of anammox bacteria based on the clone library analysis of 16S rRNA genes by 3% cutoff, and the copy numbers of hzsB genes along depth profiles of three paddy soils.…”
Section: Detection Of Anammox Bacteria In Paddy Soilsmentioning
confidence: 95%
“…Therefore, it is not surprising that Candidatus Scalindua was absent but Candidatus Brocadia and Kuenenia were predominant in paddy soils in this study. Recent investigations have also demonstrated the wide prevalence of these two genera in paddy soils (Bai et al, 2015) and dry agricultural soils (Shen et al, 2013) across broad areas of China. Observations from laboratory-scale experiments indicated that Candidatus Brocadia had relatively higher tolerance to O 2 and a higher growth rate (Oshiki et al, 2011).…”
Section: Detection Of Anammox Bacteria In Paddy Soilsmentioning
confidence: 99%
See 2 more Smart Citations